Kesesuaian Penilaian Keterampilan Komunikasi Interpersonal Mahasiswa Kebidanan Antara Pembimbing Klinik dan Pasien - Nita Nurvita (STIKes Karsa Husada Garut, 2018)
Assessment of student’s communication skill is one of the prime assessments in midwifery education process. This assessment is conducted to measure student’s accomplishment towards learning objectives designated by the academic institution. Involvement of patient in the assessment process is important to conduct to know the student’s communication skill from service user, whereas the involvement of clinic instructor is aimed to provide guidance and as an evaluator. Thus, this research aimed to assess the compatibility of interpersonal communication assessment of midwifery student between clinic instructor and patients. This research is a quantitative research with cross sectional design. The total of research subjects were 122 respondents, consist of 49 midwifery students of Poltekkes Tasikmalaya who are on clinical practice activity, 49 pregnant women, and 24 clinic instructors. This research was conducted at 24 private maternity clinics in Tasikmalaya on September 2013. Communication skill of midwifery students were measured using Likert scale with 11 statements. There are three aspects of assessment in this research which consist of raising problems and worries, disease management explanation and patient involvement in decision making. The compatibility of midwifery student’s communication skill between clinic instructor and patients is measured by Cohen Kappa consistency test. It is interpreted as having significant result when p-value is <0.05. The analysis result showed a-Kappa index of 0.23 and p-value<0.01, indicating a weak level of agreement between clinic instructor and patients on assessing communication skill of midwifery students. Based on research result, it can be concluded that either clinic instructor or patients can be involved in interpersonal communication skill evaluation among midwifery students. However, a-careful evaluation is needed when patients are involved especially in relation to their background characteristics and their ability to use the instruments. As recommendation, qualitative research should be conducted to find out more important aspects of interpersonal communication skill to further enhance communication skills curricula for midwifery students.